WATER QUALITY ASSESSMENT OF EUPHRATES RIVER IN QADISIYAH PROVINCE (DIWANIYAH RIVER), IRAQ - & Hassan, Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted to assess the water quality of the Diwanyiah River by the water quality Index (WQI) over the period from September 2015 to June 2016. Four sites were selected along the river. The Canadian water Quality Guideline- water Quality Index (CCME-WQI) was applied to the Diwanyiah River in this study. Nine environmental parameters (water temperature, power of Hydrogen ion, dissolved oxygen, total dissolved solids, turbidity, total alkalinity, nitrite, nitrate and phosphate) were selected to assess the water quality for the protection of aquatic life. The water quality index results showed that the water quality of the river is ranged between poor to marginal.